2020
DOI: 10.21203/rs.3.rs-76807/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Diet and Lifestyle Changes During COVID-19 Lockdown in the United Arab Emirates: Results of a Cross-Sectional Study

Abstract: Background: Lockdown measures were implemented in many countries to limit the spread of the COVID-19 pandemic. However, such restrictions could precipitate unintended negative consequences on lifestyle behaviors. The main objective of this study was to investigate the prevalence and determinants of unhealthy behavior changes during the COVID-19 lockdown among residents of the United Arab Emirates (UAE).Methods: A cross-sectional web-based survey of adults residing in the UAE was carried out during lockdown (n=… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 27 publications
(31 reference statements)
2
18
0
Order By: Relevance
“…It can be said that, in general, there is sensitivity towards the consumption of healthier diets in the pandemic. However, other works mentioned opposite attitudes, as the study of Rawdan et al (2020) in United Arab Emirates, where non healthy eating habits increased during the COVID-19 contingency, being the most common increased food intake.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…It can be said that, in general, there is sensitivity towards the consumption of healthier diets in the pandemic. However, other works mentioned opposite attitudes, as the study of Rawdan et al (2020) in United Arab Emirates, where non healthy eating habits increased during the COVID-19 contingency, being the most common increased food intake.…”
Section: Discussionmentioning
confidence: 98%
“… Radwan et al (2020) stated that cooking at home could change dietary habits. Bad eating habits are undoubtedly a problem that needs multiple solutions, that involve individual awareness where families play a relevant role but it is also a government concern.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have shown that during the COVID-19 quarantine period, there was an increase in unhealthy living behaviors, such as a decrease in physical activity and malnutrition, an increase in weight gain, and an increase in smoking [29][30][31]. In addition, one study noted that school closures would have a lasting impact on nutritional and lifestyle behavior and long-term challenges for children.…”
Section: Discussionmentioning
confidence: 99%